Assessment of winter hardiness of common hazel (Corylus avellana L.) in Voronezh region depending on forest conditions - Nakonechnaya Tatiana; Slavskiy Vasily; Tsaralunga Anna; Poddubnaya Anastasia (BIO Web of Conferences)
Abiotic factors often do not allow to realize the productivity potential of nut-bearing plants, which entails a decrease in the efficiency of their cultivation. One of the key adaptive properties of common hazel in the Voronezh region is winter hardiness, but in some cases, its determination requires long-term observations. The aim of the study was to evaluate winter hardiness of common hazel depending on forest conditions in Voronezh region using express methods. It was found that frost resistance and frost hardiness have the lowest level of significance (F=5) in determining the general winter hardiness of hazel. The highest value of Fisher’s criterion was observed for resistance to early spring frosts (F=30) and sharp temperature changes in winter (F=25). Despite the danger of spring frosts limiting cultivation of hazel in Voronezh region, the most favorable TLU - C2D and D2, where the greatest winter hardiness of plants was noted. This allows recommending wide cultivation of common hazel in these forest conditions.